Clinical presentation and outcomes of COVID‐19 following hematopoietic cell transplantation and cellular therapy. Issue 4 (2nd May 2021) - Camargo, Jose F.; Mendoza, Maria A.; Lin, Rick; Moroz, Ilona V.; Anderson, Anthony D.; Morris, Michelle I.; Natori, Yoichiro; Natori, Akina; Raja, Mohammed; Lekakis, Lazaros; Beitinjaneh, Amer; Jimenez, Antonio; et al.
Abstract: Background: One year into the pandemic, published data on hematopoietic cell transplantation (HCT) recipients with coronavirus disease 2019 (COVID‐19) remain limited. Methods: Single‐center retrospective cohort study of adult HCT recipients with polymerase chain reaction (PCR)‐confirmed severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection. Results: Twenty‐eight consecutive transplantation and cellular therapy patients (autologous, n = 12; allogeneic, n = 15; chimeric antigen receptor T‐cell therapy [CAR‐T], n = 1) with COVID‐19 were identified. The median age was 57 years. The median time from HCT to COVID‐19 diagnosis was 656 days (interquartile range [IQR], 33‐1274). Patients were followed for a median of 59 days (IQR, 40‐88). Among assessable patients (n = 19), 10 (53%) had documented virological clearance; median time to clearance was 34 days (range, 21‐56). Out of 28, 12 (43%), 6 (21%), and 10 (36%) patients had mild, moderate, and severe/critical disease, respectively. Overall mortality was 25%, nearly identical for autologous and allogeneic HCT, and exclusively seen in hospitalized patients, older than 50 years of age with severe COVID‐19. None of the patients with mild (n = 12) or moderate (n = 6) COVID‐19 died whereas 7/10 patients (70%) with severe/critical COVID‐19 died ( P = .0001). Patients diagnosed with COVID‐19 within 12 months of HCT exhibited higher mortality (57% vs 14%; P = .04). All‐cause 30‐day mortality (n = 4) was 14%. A higher proportion of patients who died within 30 days of COVID‐19 diagnosis (3/4) were receiving ≥2 immunosuppressants, compared with patients who survived beyond 30 days after COVID‐19 diagnosis (2/24; 75% vs. 8%; P = .01). Conclusions: Mortality in COVID‐19 HCT patients is higher than that of the age‐comparable general population and largely dependent on age, disease severity, timing from HCT, and intensity of immunosuppression.